Peningkatan Produktivitas Pada Lini Perakitan Stopper Crash Stop Dengan Otomatisasi Mesin Produksi - Qomarotun Nurlaila (SIGMA TEKNIKA, 2022)
PT. ABC is a Japanese PMA that produces HDD (Hard Disk Drive) components, where the assembly process still uses a partial automatic machine whose productivity still depends on the performance of the operator to do manual work. This research aims to increase the productivity of HDD products on the assembly line. The research design used is a combination of exploratory and descriptive methods. Its research approach uses quantitative data. The variable of this study is productivity, the type of data used is primary data and secondary data. The method to increase productivity on the Crash Stop assembly line is to eliminate manual work and change the assembly machine (assemble rubber and stainless components) from partially automatic to fully automatic. The result after replacing the assembly machine from partially automatic to fully automatic was that productivity increased by 2.5 times compared to the previous one which was an increase of 4,707 pieces / person / hour (from 1,913 to 6,620 pieces / person / hour). From the research that has been done, it can be concluded that productivity on the assembly line increases after the replacement of the machine from a partially automated machine to a fully automatic machine.  In the future, it is expected that automatic machines can be applied to other production machines.